Temperature behaviour of the yellow emission in GaN - Seitz, R. (2012)
Even in good quality undoped GaN samples, as assessed by the intense excitonic emission, the yellow band is present. This band has been attributed either to a shallow donor to deep double donor pair recombination [1], to a deep donor to a shallow acceptor [2] or to a shallow donor and a deep state [3]. However, its origin is not yet clear. We present data on time resolved spectroscopy compared with steady state results. These results indicate that there is no difference in band shape between steady state and time resolved spectra at all temperatures. However, in some samples there is an increase in intensity of the yellow band. It is concluded that besides a fast emission, due to prompt excitation of the centre, an indirect path from a trap 13.7 meV below the shallow donor is responsible for the long component of the decay and the intensity increase. An emission with a lifetime of ca. 300 ms is also present with a maximum at 2.35 eV.